Refined estimates for the ε-entropy of the classes $KH_0^α$ - Tyrygin, I. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By the methods of differential pulse-code modulation and “generalized” polygonal lines, we obtain almost exact estimates for the ɛ-entropy of classes simulating signals of various types. The complexity of coding and reconstruction of functions from the classes under consideration is investigated. We present a numerical solution of the problem of minimization of constants in the order-of-magnitude inequality for the ɛ-entropy of the classes $KH_0^α$.